The Importance of Electron Landau Damping for the Dissipation of Turbulent Energy in Terrestrial Magnetosheath Plasma. Issue 12 (21st December 2021) - Afshari, A. S.; Howes, G. G.; Kletzing, C. A.; Hartley, D. P.; Boardsen, S. A.
Abstract: Heliospheric plasma turbulence plays a key role in transferring the energy of large‐scale magnetic field and plasma flow fluctuations to smaller scales where the energy can be dissipated, ultimately leading to plasma heating. High‐quality measurements of electromagnetic fields and electron velocity distributions by the Magnetospheric Multiscale (MMS) mission in Earth's magnetosheath present a unique opportunity to characterize plasma turbulence and to determine the mechanisms responsible for its dissipation. We apply the field‐particle correlation technique to a set of 20 MMS magnetosheath intervals to identify the dissipation mechanism and quantify the dissipation rate. It is found that 95% of the intervals have velocity‐space signatures of electron Landau damping that are quantitatively consistent with linear kinetic theory for the collisionless damping of kinetic Alfvén waves. About 75% of the intervals contain asymmetric signatures, indicating a local imbalance of kinetic Alfvén wave energy flux in one direction along the magnetic field than the other. About one‐third of the intervals have an electron energization rate with the same order‐of‐magnitude as the estimated turbulent cascade rate, suggesting that electron Landau damping plays a significant, and sometimes dominant, role in the dissipation of the turbulent energy in these magnetosheath intervals. Key Points: Electron Landau damping plays a ubiquitous role in dissipating Alfvénic turbulent energy in the magnetosheath Electron Landau damping signatures correspond to the wave energy flux direction, implying the dissipation of locally imbalanced turbulence Electron Landau damping sometimes plays a dominant role in dissipating turbulent energy in the magnetosheath